Inhibitory Activity of Pyrroloisoxazolidine Derivatives against Chlamydia trachomatis. (15th March 2021) - Ni, Min; Xu, Shunxin; Liu, Ziyi; Xue, Yin; Xie, Wenxia; Yang, Shengju; Liu, Lingyan; Bao, Xiaofeng
Abstract : The obligate intracellular bacterium Chlamydia trachomatis is a group of worldwide human pathogens that can lead to serious reproductive problems. The frequent clinical treatment failure promoted the development of novel antichlamydial agents. Here, we firstly reported a group of pyrroloisoxazolidine-inhibited C. trachomatis in a dose-dependent manner in vitro . Among them, compounds 1 and 2 exhibited the strongest inhibitory activity with IC50 values from 7.25 to 9.73 μ M. The compounds disturbed the whole intracellular life cycle of C. trachomatis, mainly targeting the middle reticulate body proliferation stages. Besides, the compounds partially inhibited the chlamydial infection by reducing elementary body infectivity at high concentration. Our findings suggest the potential of pyrroloisoxazolidine derivatives as promising lead molecules for the development of antichlamydial agents.